Performance Evaluation of a Single Cylinder Spark Ignition Engine Fuelled by Mixing Ethanol and Gasoline - A.S. Olawore; W.I. Oseni; K.O. Oladosu; E.O. Fadele (Journal of Applied Sciences and Environmental Management, 2021)
The use of ethanol blend as an alternative source of fuel for developing clean and sustainable energy sources has grown considerably. In this study, the performance characteristics of an air-cooled, single-cylinder 4-stroke Spark Ignition (SI) engine (TD201) with a compression ratio of 8.5:1 was determined using gasoline and different blend ratios of ethanol and gasoline (E0, E2, E4, E6, E8, E10, and E12) at a varied engine speed of 2000rpm, 2200rpm, 2400rpm, 2600rpm and 2800rpm. The results revealed that as the ethanol content of the blend increases, the heating value decreases while octane value increases. The experimental results indicated that the brake torque, and power increase as the ethanol content in the blends increases. However, BSFC and exhaust temperature decreases as the ethanol content in the blends increases because of the oxygen enrichment. The emissions of unburned hydrocarbon and carbon monoxide reduce while carbon dioxide and ethanol content increases when compared with the reference fuel (E0).